5-Azacytidine: Microbiological Assay in Mouse Blood - Pittillo, Robert F. (1969)
A 6-chloropurine-resistant strain of Escherichia coli has been used to develop a microbiological assay for the estimation of 5-azacytidine distribution in mouse tissues.